Estudio de prefactibilidad para la exportación de Cacao en grano al mercado de Bélgica - Gonzalez Escobar, Maria Alejandra; Trujillo Urueña, Maria Angelica (Universidad Antonio Nariño, 2022)
The purpose of this pre-feasibility study is to determine the feasibility of exporting cocoa beans from the department of Tolima to Belgium, where we want to take advantage of the conditions offered by this country due to its chocolate tradition, in addition to the characteristics and benefits provided by the national product known as fine aroma, which makes it recognized worldwide for its quality and natural origin.